Islamic sukuk industry in the Arab world between the leadership of countries and the start of other countries - Analytical study of a group of Arab experiences- - Ayache, Zoubier; Fenazi, Fatima Zahra (Finance and Business Economies Review, 2019)
This study examines the reality of the Islamic Sukuk industry in the Arab countries. The objective of this paper is to investigate the factors and reasons behind the success of sukuk industry in some Arab countries by presenting and analyzing the leading Arab experiences in this field, to benefit from their expertise for other countries seeking to establish and develop a market for the industry Islamic Sukuk, which is one of the most prominent Islamic financing tools, It is a legitimate financing tool that absorbs great economic potentials, which can be applied for various purposes, including: use as a tool of monetary policy to manage excess liquidity, And the financing of the resources of Islamic financial institutions and economic institutions.